Advanced Heliopol/Stratimat Composite Laminate Material Behavior under Cyclic Bending Loads. (2017) - Modrea, Arina; Teodorescu-Draghicescu, Horatiu; Szava, Ioan; Szava, Renata; Galfi, Botond
Abstract: Within this paper, the material behavior of an advanced composite laminate subjected to static cyclic bending loads have been experimentally determined on an LR5KPlus Lloyd Instruments materials testing machine. The composite laminate structure is formed of HELIOPOL 9431ATYX_LSE resin reinforced with five layers STRATIMAT300 glass fibers of 300 g/m 2 specific weight. One composite specimen has been subjected to various deflection limits to determine its hysteresis behavior. The results show a maximum hysteresis towards 14 mm upper deflection limit.